On some Diatoms from High Altitude Gokyo Lake-Iii, Sagarmatha National Park, Nepal - Rai, Shiva Kumar; Mishra, Pradeep Kumar; Madan, Kamal (Journal of Natural History Museum, 2015)
The present paper describes total 16 taxa of diatoms under 12 genera, belonging to 1 centric (Cyclotella antiqua W. Smith var. minor Suxena & Venkateswarlu) and 15 pennate species from Gokyo lake- III, Sagarmatha National Park, Nepal. Of these, 6 were the new records for the country. The morphological descriptions, taxonomic accounts and distribution are described systematically with photographs J. Nat. Hist. Mus. Vol. 26, 2012: 93-110